Analisis Gaya Bahasa dalam Buku Atomic Habits Karya James Clear - Isamaya Nurhayati; Radiah U. Gorotomole (Kajian Administrasi Publik dan ilmu Komunikasi, 2024)
This study aims to analyze the language style contained in the book Atomic Habits by James Clear which has been translated into Indonesian by Alex Tri Kantjono Widodo. The method used in this study is descriptive analysis with literature study. The results of the analysis show that the book is presented in a simple and easy-to-understand language style so that readers do not feel burdened when reading more than 300 pages. The delivery of the content of this book makes it more relaxed and interesting. This writing style not only makes the material easy to understand, but also encourages readers to apply the values in the book for them to apply in their lives.